2018
DOI: 10.1136/bmjopen-2017-019040
|View full text |Cite
|
Sign up to set email alerts
|

Manual therapy for unsettled, distressed and excessively crying infants: a systematic review and meta-analyses

Abstract: ObjectiveTo conduct a systematic review and meta-analyses to assess the effect of manual therapy interventions for healthy but unsettled, distressed and excessively crying infants and to provide information to help clinicians and parents inform decisions about care.MethodsWe reviewed published peer-reviewed primary research articles in the last 26 years from nine databases (Medline Ovid, Embase, Web of Science, Physiotherapy Evidence Database, Osteopathic Medicine Digital Repository, Cochrane (all databases), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 46 publications
4
36
0
2
Order By: Relevance
“…Our evidence rating is similar to the recent 2018 systematic review and meta-analysis of infantile colic and manual therapy conducted by Carnes et al [68]. Carnes et al concluded that while small benefits were found for the overall outcome, the benefit of manual therapy for infantile colic is still unclear [68]. For pediatric enuresis, our search identified only one observational study showing favorable results; however, this level of evidence was not enough to substantiate a “favorable” rating [25].…”
Section: Discussionsupporting
confidence: 89%
“…Our evidence rating is similar to the recent 2018 systematic review and meta-analysis of infantile colic and manual therapy conducted by Carnes et al [68]. Carnes et al concluded that while small benefits were found for the overall outcome, the benefit of manual therapy for infantile colic is still unclear [68]. For pediatric enuresis, our search identified only one observational study showing favorable results; however, this level of evidence was not enough to substantiate a “favorable” rating [25].…”
Section: Discussionsupporting
confidence: 89%
“…There were no serious adverse events reported for either probiotics or manual therapy, indicating that both represent a low risk to infants, although we cannot conclude they are without any risk 27 42. Two reviews16 43 analysed the risks of adverse events with manual therapy, one showed 88% less risk of an adverse event in the manual therapy groups than in the control groups43 and the other showed one in six parents reported non-serious adverse events 16. Another study42 reported data from non-RCTs which included four case studies reporting serious incidents of harm but there was some doubt over causality as a result of the treatments given.…”
Section: Discussionmentioning
confidence: 89%
“…Several nonmedical interventions have been developed to both decrease infant crying and support parents concerned about infant crying (Akhnikh et al, ). For example, manual therapies may provide small positive benefits in reducing the duration of crying (Carnes, Plunkett, Ellwood, & Miles, ), and interventions focusing on strategies to prevent parents from harming their baby have also been proposed (Barr et al, ). Some interventions, for example, behavioural therapy (Powell et al, ), have been developed to support parental sensitivity in dealing with excessive crying or to improve interactions and communication between parents and infants (Akhnikh et al, ; Blom, van Sleuwen, de Vries, Engelberts, & L'hoir, ).…”
Section: Discussionmentioning
confidence: 99%